MicroRNA‐135a‐3p regulates angiogenesis and tissue repair by targeting p38 signaling in endothelial cells. Issue 4 (22nd January 2019) - Icli, Basak; Wu, Winona; Ozdemir, Denizhan; Li, Hao; Haemmig, Stefan; Liu, Xin; Giatsidis, Giorgio; Cheng, Henry S.; Avci, Seyma Nazli; Kurt, Merve; Lee, Nathan; Guimaraes, Raphael Boesche; et al.
ABSTRACT: Angiogenesis is a critical process in repair of tissue injury that is regulated by a delicate balance between pro‐ and antiangiogenic factors. In disease states associated with impaired angiogenesis, we identified that miR‐135a‐3p is rapidly induced and serves as an antiangiogenic microRNA (miRNA) by targeting endothelial cell (EC) p38 signaling in vitro and in vivo . MiR‐135a‐3p overexpression significantly inhibited EC proliferation, migration, and network tube formation in matrigel, whereas miR‐135‐3p neutralization had the opposite effects. Mechanistic studies using transcriptomic profiling, bioinformatics, 3′‐UTR reporter and miRNA ribonucleoprotein complex ‐immunoprecipitation assays, and small interfering RNA dependency studies revealed that miR‐135a‐3p inhibits the p38 signaling pathway in ECs by targeting huntingtin‐interacting protein 1 (HIP1). Local delivery of miR‐135a‐3p inhibitors to wounds of diabetic db/db mice markedly increased angiogenesis, granulation tissue thickness, and wound closure rates, whereas local delivery of miR‐135a‐3p mimics impaired these effects. Finally, through gain‐ and loss‐of‐function studies in human skin organoids as a model of tissue injury, we demonstrated that miR‐135a‐3p potently modulated p38 signaling and angiogenesis in response to VEGF stimulation by targeting HIP1. These findings establish miR‐135a‐3p as a pivotal regulator of pathophysiological angiogenesis and tissue repair by targeting a VEGF‐HIP1‐p38K signaling axis, providing new targets for angiogenic therapy to promote tissue repair.—Icli, B., Wu, W., Ozdemir, D., Li, H., Haemmig, S., Liu, X., Giatsidis, G., Cheng, H. S., Avci, S. N., Kurt, M., Lee, N., Guimaraes, R. B., Manica, A., Marchini, J. F., Rynning, S. E., Risnes, I., Hollan, I., Croce, K., Orgill, D. P., Feinberg, M. W. MicroRNA‐135a‐3p regulates angiogenesis and tissue repair by targeting p38 signaling in endothelial cells. FASEB J. 33, 5599–5614 (2019). www.fasebj.org